Fermentable oligosaccharides, disaccharides, monosaccharides and polyols: role in irritable bowel syndrome. (September 2014) - Tuck, Caroline J; Muir, Jane G; Barrett, Jacqueline S; Gibson, Peter R
<x xml:space="preserve">Abstract</x> Irritable bowel syndrome (IBS) was previously left poorly treated despite its high prevalence and cost. Over the past decade, significant research has been conducted providing new dietary strategies for IBS management. The 'low fermentable oligosaccharides, disaccharides, monosaccharides and polyols diet' has shown symptom improvement in 68–76% of patients. Randomized, controlled trials have now proven its efficacy. The diet, low in poorly absorbed and fermentable carbohydrates, uses dietary restriction and re-challenge to determine individual tolerance to various short-chain carbohydrates. However there may be potential detrimental effects of the diet in the long term, due to potential changes to the gastrointestinal microbiota. Appropriate dietary education and management of the diet is imperative. Future research should focus on the relevance of changes to the microbiota and ways to liberalize the dietary restrictions.